Tasmanian convict sentence book (1847)
A record of convict sentences passed at Hobart, 1847. There is only part of the volume.
Manuscript reference: NLA MS 3445.
Sir John Ferguson Collection.
Keywords: Convicts -- Tasmania -- Registers; Convicts